2015
DOI: 10.3126/nelta.v19i1-2.12076
|View full text |Cite
|
Sign up to set email alerts
|

Use of ICT/Web Tools in ELT in Nepal

Abstract: Information and Communication Technology (ICT) has become the integral part of English Language Teaching (ELT) to meet the needs of the present day world. It has brought significant changes in the traditional teacher-centered lecturing methods. However, this emerging field of study has not been researched rigorously in the context of Nepal. Considering this, the research study carried out at the Department of English Education, Tribhuvan University, Kathmandu aimed to find out the commonly used ICT/Web tools i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 5 publications
(1 reference statement)
1
13
0
Order By: Relevance
“…As these studies show, little research has been done on the digital literacy skills of the EFL teachers in the world. Although a few studies have focused on using ICT with teaching language in Nepal (Acharya, 2014;Thapaliya, 2014;Rana et al, 2018), there has been no research on school-level EFL teachers' digital literacy in Nepal. In this context, the current study sheds new light compared to existing studies, especially in Nepal.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As these studies show, little research has been done on the digital literacy skills of the EFL teachers in the world. Although a few studies have focused on using ICT with teaching language in Nepal (Acharya, 2014;Thapaliya, 2014;Rana et al, 2018), there has been no research on school-level EFL teachers' digital literacy in Nepal. In this context, the current study sheds new light compared to existing studies, especially in Nepal.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regarding the previous studies on ICT, they have shown the need of ICT integration in ELT. Acharya's (2013) study in Nepal indicated that ICT in ELT classrooms supports learner autonomy, more effective and efficient classroom activities. Similarly, studies in ICT in Nepal also explored that use of ICT motivates students towards lesson; makes them more creative, analytical, and constructive (Thapaliya, 2014& Jha, 2017.…”
Section: Ict Integration In Teaching and Learning Englishmentioning
confidence: 99%
“…The above description clearly indicated that ICT devices helped them maximize learners' engagement for correct pronunciation, learning new meanings and listening practice in which they are unfamiliar. They can learn many things and share to each other collaboratively as ICT provides them access and support to teacher professional development (Acharya, 2013).…”
Section: Teacher Professional Development (Tpd) Supportmentioning
confidence: 99%
“…A lack of useful means of communication in the community schools was one of the barriers to access the schools. The very real digital divide between community schools and private schools (Acharya, 2015) means that any researchers would face numerous difficulties similar to mine in accessing rural schools. This situation compelled me to travel directly to the DEOs, NGOs and local schools in different districts to find the right sample schools.…”
Section: Planning and Setting Outmentioning
confidence: 99%